Utilization of fermented coffee husk feed using Aspergilus niger on histological features of tawes (Barbonymus gonionotus) - Desy Nurrahma Dhani; Lenni Fitri; Firdus Firdus (Depik, 2024)
Coffee husk is one of the resources that has the potencial to be used as raw material for tawes (Barbonymus gonionotus) feed. The addition of Aspergillus niger in this study is known to increase the protein content of coffee husk from 15.99% to 21.75%. This study aims to determine the effectiveness of giving fermented coffee husk using Aspergillus niger on the histology of Tawes intestine. This study used a completely randomized design (CRD) with 5 treatments of coffee husk addition, namely 0%, 10%, 20%, 30%, and 40%, and 4 repetitions. The results showed that the addition of 30% fermented coffee husk into the feed produced the best intestinal histology picture with an average value of villi height of 243.21 40.02 m, basal width of 79.77 30.77 m and apical width of 69.09 14.61 m.Keywords:FermentationCoffee HuskBarbonymus gonionotusTawesAspergilus niger